Review of Syariah Economic Law on Digitalization of Zakat: Case Study of the Kitabisa.com Platform - Qayla Nur’ Aini; Muthoifin (proceedings.icesy, 2026)
The development of digital technology is driving transformation in zakat management, including through online platforms such as Kitabisa.com. This paper aims to examine the practice of digitizing zakat through Kitabisa.com in the perspective of sharia economic law. The method used is the study of normative law with a conceptual and legislative approach. The data was obtained through a library study of perimer, secondary and tertiary legal materials related to zakat and digital transactions. The results of the study show that the practice of digital zakat through Kitabisa.com is allowed in Zyariah as long as it meets the principles and conditions of zakat and is carried out through a legitimate contract mechanism, namely your akad (s) and wakalah. This practice is also in line with Law No. 23 of 2011 on the management of zakat and potentially supports the achievement of sharia maqashid goals. Therefore, it is necessary to increase transparency, sharia compliance, and zakat digital.